The religious system of the Ndlambe of East London district - Bigalke, Erich Heinrich (Rhodes University, Faculty of Humanities, Department of Anthropology, 1970)
From conclusion: This study has had a twofold objective, to present ethnographic data on a people who belong to the Xhosa tribal cluster and more specifically, to throw light on aspects of the ancestor cult among the Xhosa. In particular an attempt has been made to explore the nature of the interrelation between the social structure and the ancestor cult. Attention has been focussed on the lineage as an institution, on the rituals devoted to the ancestors and on the means of explaining misfortune. Though the Ndlambe, in common with other groups of indigenous people in the Eastern Cape, have been experiencing developments brought about by social change during the better part of two centuries, the recent implementation of the Betterment Scheme has resulted in drastic demographic changes. The former settlement pattern of scattered homesteads has given way before village formation. Beyond the fact that it has resulted in the closer proximity of homesteads, with the opportunities for cooperation and conflict that this situation implies, nothing is known of the direct organizational influence of this development. More"¦
Keywords: Xhosa (African people) -- Religion